Characteristics and Problems of Professional Development of Teachers in the Balkan Countries - Vučinić, Dragiša S.; Đurić, Igor R.; Andrić, Aleksandra M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
It is generally accepted that the quality of teaching significantly contributes to the quality of the entire educational process. One of the key factors in the quality of teaching is the teacher, whose characteristics, roles, teaching style, and also professional development are always the subject of research, not only in pedagogy but also in other social and humanistic sciences. This paper presents the characteristics and problems of the professional development of teachers in several Balkan countries. The comparative-critical analysis was performed on the programs of professional development of teachers in our country and the programs in Montenegro, Northern Macedonia, BiH, Croatia, Bulgaria, Greece, and Albania. The aim of the analysis was to determine the characteristics of the mentioned programs, their similarities and differences, as well as possible problems in their organization and implementation, which would help improve the professional development of teachers in our country. The comparative analysis determined that the professional development of teachers in the Balkan countries is prescribed by appropriate laws and regulations. Numerous opportunities for professional development of teachers were identified in various educational programs, which led to conclusion that the mentioned programs follow the reform processes in the field of education. Considering that the professional development of teachers is directed towards the future development of society, it is necessary to mention the need for continuous empirical research in this area, the results of which would be helpful in a more complete understanding of the problems in educational practice.